Some chemical properties of camiyani black pine - Aytekin, Alper; Gündüz, Gökhan; Vurdu, Hasan (International Conference on Ecology and Security of Life Activity, 2003)
The aim of this study was to assess some chemical properties of Pinus nigra Arn. var. pallasiana subsp. pallasiana. This, is one of the most valued tree species used in furniture industry in Turkey. The distribution of this relict species is the Western Black Sea Region. The most important property of this tree is its straight and uniform stem and evident-large heartwood. The large heartwood content is reached up to 62,04 % of the total cross section (Gündüz, 1999). This is the most important reason for its usage in the furniture industry. Since no research has been conducted on the factors that forms the larger heartwood of Camiyani Black Pine, some chemical properties of the heartwood of his species were determined. Therefore, some chemical properties of this large heartwood contain species were carried out and compared with values from the same tree species (P. nigra Arn. var. pallasiana) which are grown in different regions of Turkey (Table 2).
Keywords: Pinus nigra Arn; Mobilya endüstrisi; Furniture industry